Laporan tesis cadangan pengubahsuaian Auto Bavaria ( M ) Showroom di No 207, Jalan Bukit Bintang, 55100, Kuala Lumpur / Mohamad Syahrul Ariff Shah - Ariff Shah, Mohamad Syahrul (Faculty of Architecture, Planning and Surveying, 2005)
The company was established in 1988. 2. Auto Bavaria is a division of Tfactors Malaysia (1982) Sdn. Bhd and a member of the Sime Darby Group. 3. Auto Bavaria provides customer with not only cars, but also motorcycles with items and services related to them. 4. There are countless cars accessories beside motorcycles. 5. Apart from all that, Auto Bavaria also provides excellent after sales service to ensure client’s needs even after the client’s purchase is met satisfaction.